A Computational program for the Newton polyhedron and the integral closure of ideals - Bíscaro, H.H.; Pisa, I.T.; Saia, M.J. (Trends in Computational and Applied Mathematics, 2000)
We describe the implementation of a computational programa that, for a given ideal with finite codimension in the ring of complex polynomials, constructs the Newton polyhedron and determines the integral closure of the ideal.